Study of the effect of the combined fungicide Abacus Ultra on the population structure of the wheat leaf rust pathogen - M. S. Gvozdeva; G. V. Volkova (Юг России: экология, развитие)
Aim. To study the variability of the intrapopulation structure of the causative agent of wheat leaf rust (Puccinia triticina Erikss.) on the basis of pathogenicity under the influence of the combined fungicide Abacus Ultra, SE.Material and Methods. The studies were carried out in the greenhouse complex of the Federal Research Center of Biological Plant Protection on the winter wheat variety Krasnodarskaya 99 which is susceptible to leaf rust. The material studied was the combined fungicide Abacus Ultra, SE with application rates of 0.75; 1.0; 1.25; 1.5; 1.75 l/ha. The work was carried out according to generally accepted methods.Results. The influence of the impact of different rates of application of the fungicide Abacus Ultra, SE on the average virulence of the P. triticina population was established, this indicator varying from 40.0% (control [without treatment]) to 19.5% (fungicide application rate 1.75 l/ha). As a result of the analysis of the phenotypic composition of the population, 5 phenotypes were identified. A decrease in the viability of spores of the fungus P. triticina with an increase in the rate of application of the fungicide was established, this indicator varying from 69.1% (0.75 l/ha) to 29.2% (1.75 l/ha). A decrease in the aggressiveness of the population of the causative agent of leaf rust with an increase in the rate of application of the drug was established. The biological effectiveness of the fungicide Abacus Ultra, SE against the pathogen was 95.3–97.8% at the recommended application rate of 1.0–1.5 l/ha.Conclusion. The study showed that the population of the leaf rust pathogen treated with the chemical fungicide Abacus Ultra, SE is characterised by a change in structure in terms of aggressiveness and virulence, while the sensitivity remains high due to the combination of the active substances pyraclostrobin and epoxiconazole with a different mechanism of action in the preparation.